Attempts to apply heuristic research methodology in mechanical engineering on the example of rotating machines - Kiciński, Jan; Żywica, Grzegorz (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
On any website or in encyclopaedias such as Britannica or Wikipedia, under the entry ‘heuristics,’ one can find numerous definitions, references, and examples from various areas of life. However, the authors of this article have been unable to find examples relevant to technology, particularly in mechanical engineering. This fact inspired us to address this topic, especially since many concrete examples from practice and everyday life seem well-suited to demonstrating the relevance of heuristic methodologies in technical sciences. According to the authors, turbomachinery appears to be of particular interest in this context. This is critical machinery, i.e., machinery whose failure threatens human life. Hence the importance of developing advanced tools to analyze them, especially across the entire operating range (both stable and unstable). With these tools, one can effectively use their intellect, intuition, and common sense in the decision-making process. A classic heuristic symbiosis is thus formed. The paper demonstrates an advanced computer system called MESWIR, developed at the Institute of Fluid-Flow Machinery of the Polish Academy of Sciences in Gdańsk (IMP PAN), which generates a range of interesting diagnostic information, including multiple whirls and stochastic errors related to the unbalance vector. The research was conducted using high-speed, low-power turbines as examples. Although there is no formal theoretical proof of their correctness, the results obtained facilitate drawing the right conclusions and making informed decisions, which is the essence of decision-making heuristics.